Dinosaurs their discovery and their world - Colbert, Edwin H. (Edwin Harris) 1905-2001 (Dutton, 1961)
Dr. Colbert describes the individual types of dinosaurs, and presents accounts of scientists, past and present, who have collected and studied them. A classification of the dinosaurs, arranged geologically and geographically, is included.